PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN MODEL PICTURE AND PICTURE PADA PELAJARAN BAHASA INDONESIA - Wulandari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is aimed to overcome the lack of the studying results of the writing poem subject in the class V SDN 20 Pontianak Selatan,by using picture and picture method it can make them easier in writing poems. The method that using in this research was Descriptive method in form Classroom Action Research and colaborative by refered to the Classroom Action Research as, planning, observation, and reflection. The subject of this research was students of class V SDN 20 Pontianak Selatan in this research were 25 students of class V semester 2 academic year 2017/2018. Data collecting techniques in this research were observation,data analysis, and averege. This research result found there was improvement, (a ) teacher ability in make a palnning to writing poem by using pictures and pictures model on cycle 1 is 2,28(good enough). In cycle 2 is 3,28 ( good ), then in cycle 3 is 3,55 ( very good ). (b) the teacher ability in implementing write poem by using picture and picture poem in cycle 1 is 3,15 (good enough), cycle 2 is 3,28 (good ), cycle 3 is 3,70 ( very good ). ( c ) increasing students’ ability in write poem by using picture and picture model we can see in cycle 1 average = 67 (good enough), cycle 2 average = 71(good ),cycle 3 average = 80 ( very good ). In the other words, picture and picture model in this research in Bahasa indonesia in class V of SDN 20 Pontianak Selatan is success.Keywords: Writing Skill, Pictures and Pictures Model, Bahasa Indonesia.